The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcp.27157
|View full text |Cite
|
Sign up to set email alerts
|

Cell shape alteration during adipogenesis is associated with coordinated matrix cues

Abstract: Obesity has become one of the leading pathophysiologic disorders in recent years. Adipose tissue is the main tissue related to obesity and is known to play a role in various physiological complications, including type 2 diabetes. To better understand how the fat tissue develops, we used an in vitro live cell imaging system to quantify the adipogenesis by means of nondestructive digital imaging to monitor the accumulation of intracellular lipid droplets (LDs), a hallmark of adipogenesis, from the macro- to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 68 publications
7
69
0
Order By: Relevance
“…The results indicated an increase in the Hippo-signaling pathway as represented by the nuclear mechano-sensors YAP1 and Lamin A/C with an increase in the niche rigidity (Figure 4). These findings support the idea that static stretched conditions lead to accelerated adipogenesis (Hara et al, 2011;Lustig et al, 2018;Mor-Yossef Moldovan et al, 2019;Shoham & Gefen, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results indicated an increase in the Hippo-signaling pathway as represented by the nuclear mechano-sensors YAP1 and Lamin A/C with an increase in the niche rigidity (Figure 4). These findings support the idea that static stretched conditions lead to accelerated adipogenesis (Hara et al, 2011;Lustig et al, 2018;Mor-Yossef Moldovan et al, 2019;Shoham & Gefen, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…week. Differentiation was induced when the cultures reached a confluence of approximately 90% according to the protocol described in an earlier publication (Mor-Yossef Moldovan et al, 2019).…”
mentioning
confidence: 99%
“…In this study, we also described a new concept of adding NPs into the production process of the biocomposites in order to serve as a delivery system, for example by conjugating NPs and growth factors for biological and chemical signals in the scaffold. We demonstrated endocytosis uptake of FITC-NPs by the cells and following our earlier study, we reported that NPs could induce gene activation, proliferation, and differentiation in human mesenchymal cells [29]. We followed mesenchymal cells uptake of the FITC labeled NPs and evaluated their effect on cell viability and morphology in a 3D biocomposite and in 2D in-vitro systems over time.…”
Section: Discussionmentioning
confidence: 53%
“…As the experiment progressed and the LDs accumulated further, the mean cell projected area increased (Figs. 3f and 3g) , 2018;Lustig et al, 2018aLustig et al, , 2018b. The lipid contents in a specific FOV increased during the differentiation process (Fig.…”
Section: Monitoring Adipocyte Differentiation At the Single-cell Levelmentioning
confidence: 99%